Personalized biological treatment with lanadelumab in a patient with recurrent attacks of hereditary angioedema - Artur Gęsicki; Maciej F. Kozlowski; Karolina Żurawska; Weronika Ossowska; Jakub Sikora; Szymon Dyguś; Iwona Poziomkowska-Gęsicka (Alergologia Polska)
Hereditary angioedema (HAE) is an autosomal dominantly inherited disease caused by deficiency of C1 esterase inhibitor protein type 1 (about 85% of patients with HAE-C1-INH) or type 2 oedema (about 15% of patients with HAE-C1-INH) by C1 inhibitor dysfunction, with normal serum levels (HAE-2). Long-term treatment to prevent further attacks consists of continuous and regular administration of medications to reduce the number and severity of oedema attacks in HAE patients, thereby reducing the indirect burden of the disease. With the severe course of the disease, potentially life-threatening during flare-ups, it is expedient to implement long-term HAE attacks prophylaxis, which was very limited in Poland until September 2021.